PERAN GURU PENDIDIKAN PANCASILA DALAM MENDORONG KEAKTIFAN SISWA MELALUI METODE STUDENT CENTER LEARNING (SCL) DI KELAS X SMA BINA PUTERA KOPO - Hajar, Siti (Universitas Sultan Ageng Tirtayasa, 2022)
This research examines the role of teachers in promoting student engagement through the Student-Centered Learning (SCL) method in class X of SMA Bina Putera Kopo. Pancasila education plays a crucial role in shaping students' character and fostering active participation. The methodology used is qualitative descriptive, exploring students' subjective experiences to understand their engagement levels. Teachers act as active facilitators, creating an interactive environment that encourages student participation in discussions and expression of opinions. By assigning individual and group tasks and utilizing open discussions and case studies, teachers strive to enhance student involvement. However, challenges such as students' lack of readiness for independent learning and limited facilities hinder the learning process. Nevertheless, teachers remain focused on developing students' analytical and collaborative skills, enabling them to learn from experiences and peers.This research examines the role of teachers in promoting student engagement through the Student-Centered Learning (SCL) method in class X of SMA Bina Putera Kopo. Pancasila education plays a crucial role in shaping students' character and fostering active participation. The methodology used is qualitative descriptive, exploring students' subjective experiences to understand their engagement levels. Teachers act as active facilitators, creating an interactive environment that encourages student participation in discussions and expression of opinions. By assigning individual and group tasks and utilizing open discussions and case studies, teachers strive to enhance student involvement. However, challenges such as students' lack of readiness for independent learning and limited facilities hinder the learning process. Nevertheless, teachers remain focused on developing students' analytical and collaborative skills, enabling them to learn from experiences and peers.This research examines the role of teachers in promoting student engagement through the Student-Centered Learning (SCL) method in class X of SMA Bina Putera Kopo. Pancasila education plays a crucial role in shaping students' character and fostering active participation. The methodology used is qualitative descriptive, exploring students' subjective experiences to understand their engagement levels. Teachers act as active facilitators, creating an interactive environment that encourages student participation in discussions and expression of opinions. By assigning individual and group tasks and utilizing open discussions and case studies, teachers strive to enhance student involvement. However, challenges such as students' lack of readiness for independent learning and limited facilities hinder the learning process. Nevertheless, teachers remain focused on developing students' analytical and collaborative skills, enabling them to learn from experiences and peers.